ENHANCING STUDENT SATISFACTION IN ONLINE DISTANCE LEARNING: DEVELOPMENT OF THE E-QUALS MODEL FOR SERVICE QUALITY ASSESSMENT - Sigiyuwanta, Recsatasha; Supriyanto, Achmad (International Journal of Educational Best Practices, 2025)
Higher education service quality is a key factor in shaping student satisfaction. The era of rapidly developing technology has given birth to various innovations in the world of higher education, one of which is online distance education. These innovations must be supported by high quality services, which directly impact student satisfaction. A systematic literature review on research that examines the service quality factors of Online Distance Learning Universities from various countries will obtain a model of service quality factors in shaping student satisfaction in Online Distance Learning Universities. The purpose of this research is to identify and analyze significant service quality factors in shaping student satisfaction in Online Distance Learning Universities. In addition, this study also developed a conceptual framework in the form of a service quality model for student satisfaction in the context of distance higher education. The method used uses a qualitative approach, with the type of PRISMA (Preferred Reporting Items, for Systematic Review and Meta Analyses). The results of this study reveal that student satisfaction with service quality in Online Distance Learning Universities is influenced by various factors of service quality namely e-learning system quality, course design and content, support services, interaction, teaching & Instructor quality, and technology resources & infrastructure. The result of the research is the E-QUALS model which is a theoretical framework modeling the dimensions of service quality factors that shape student satisfaction in Online Distance Learning Universities.